Wastewater treatment (The study of Wastewater treatment plants in Riyadh in terms of treatment methods and properties of treated water) - Alghonaimi, Najla Ali (Journal of natural sciences, life and applied sciences, 2023)
This study aimed at defining the physical, chemical and bacteriological characteristics of treated wastewater in the main plants (Northern, Southern, and Al-Jazeera district) in Riyadh and comparing them with the natural, chemical and bacteriological treated wastewater characteristics stated in international and Saudi specifications and standards. Studying the variation between these plants till reaching these variables that affect negatively or positively on these characteristics. The field work was the main source of information from which the results were drawn, as a number of treated wastewater samples were collected from the three main plants in Riyadh. Conducting the necessary laboratory analyzes on such samples. The analysis included physical analyzes to estimate the acidity and alkalinity degree, the chemical analysis on chlorides, the turbidity rate, the chemical oxygen requirement, the biochemical oxygen requirement, as well as the bacterial analyzes, which included the estimation of the total number of bacteria and fecal coliform bacteria. The statistical methods were used such as arithmetic mean, graphs, and the (f) value, in order to verify the validity of research questions. The study findings reached that there were statistically significant differences in each of the scales (PH, COD, TSS, ALK, CL TURB, BOD, F.CL2) among the three main wastewater treatment plants. The study recommended the need to emphasize users of the public wastewater system not to discharge any wastewater because of its harmful effect on wastewater facilities and to oblige them to treat them to an acceptable degree.